(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Diabetes is a common disease which can lead to many serious complications including diabetic gastroparesis (DG), a chronic disorder of gastric motility which is characterized by delayed emptying of either solids or liquids from the stomach in the absence of mechanical obstruction. DG typically develops in patients with long-standing diabetes, and although it has a low incidence rate, it detracts from sufferers’ quality of life and increases rates of mortality and hospitalization. Some studies have shown a strong association between delayed gastric emptying scintigraphy (GES) and cardiovascular autonomic neuropathy; however, no study has been performed of gastric scintigraphy in diabetic patients using diabetic peripheral neuropathy as a surrogate marker. To do enable early detection of DG, our study was designed to detect the prevalence of delayed gastric scintigraphy of patients who had type 2 diabetes with peripheral neuropathy. Objective: We aimed to study the prevalence of delayed GES in type 2 diabetic patients with peripheral neuropathy without abnormal symptoms of the upper gastrointestinal (GI) tract. Study Designs: This was a pilot, prospective, cross-sectional study. Methods: Thirty cases of diabetes with peripheral neuropathy without abnormal symptoms of upper GI tract were sent for examination by GES after patients had ingested a Tc-99m tagged solid meal. Results: A total of 29 of 30 patients completed the protocol, and abnormal gastric emptying was found in 13.79% of cases. Other diabetic complications such as nephropathy and retinopathy appeared to be associated with delayed GES; however, these findings were not statistically significant. Conclusions: Delayed gastric emptying may be found even in the absence of warning symptoms. This study had limitations because of its small sample size, but it suggested that it may be possible to predict DG using diabetic peripheral neuropathy as a surrogate marker. A study with a larger sample size is required to corroborate our results.